Adjustment speed towards target capital structure and its determinants. Issue 1 (1st January 2021) - Memon, Pervaiz Ahmed; Md-Rus, Rohani; Ghazali, Zahiruddin B.
Abstract: This study examines the existence of the dynamism of capital structure in Pakistan for the period from 2003 to 2012, with specific objectives of estimating the adjustment speed and determining the factors affecting the adjustment speed towards target capital structure. Using difference Generalized Method of Moments (GMM) as the estimation technique, the study confirms the existence of optimal capital structure for Pakistani non-financial listed firms, and concludes that, depending upon the proxy of target debt used, firms make full adjustment towards optimal capital structure in 1.45 years to 2.25 years. Firms' size, profitability, stock market development, and GDP are found to be relatively consistent determinants of the adjustment speed across different proxies of debt. This study contributes in the existing literature of the capital structure by providing evidence regarding the existence of target capital structure, estimating the adjustment speed towards target capital structure, and identifies factors affecting adjustment speed towards target capital structure for Pakistan using four different measures of leverage.